Charakterystyka reliktowych lodowców gruzowych w zlewni Doliny Roztoki, Tatry Wysokie - Kisielewska, Renata (My University, 2014)
Relict rock glaciers in the High Tatra Mountains have been active during the Lateglacial of the last glaciation, when climatic conditions were suitable to development of permafrost. On base of detailed geomorphological mapping and sedimentological analysis eight relict rock glaciers in the catchment of Roztoka Valley are recognized and described. It was distinguished two types of rock glaciers: talus and moraine derived. It was described also several other discrete debris accumulations which do not fit to criteria of rock glacier

Reliktowe lodowce gruzowe w Tatrach Wysokich to formy, które były aktywne podczas schyłku ostatniego zlodowacenia, kiedy był tam możliwy rozwój wieloletniej zmarzliny. Na podstawie szczegółowego kartowania geomorfologicznego i analizy sedymentologicznej rozpoznano i scharakteryzowano osiem formy reliktowych lodowców gruzowych w zlewni doliny Roztoki, a także inne formy akumulacji gruzu, które nie spełniają kryteriów lodowca gruzowego. Wyróżniono lodowce gruzowe o genezie morenowej i piargowej.
Characteristics of relict rock glaciers in the Roztoka Valley catchment, High Tatra Mts
Keywords: rock glaciers; lodowce gruzowe; moraines; moreny; Tatra Mountains; Tatry Wysokie; late glacial; późny glacjał; glacial geomorphology; geomorfologia glacjalna